Stress production by Cebuano learners of Arabic: A metrical analysis - Huneety, Anas; Mashaqba, Bassil; Al-Quran, Majed; Hishma, Jehan (Indonesian Journal of Applied Linguistics, 2020)
Stress is one of the most neglected components of the Arabic language in classrooms (Lin, 2018; Ryding, 2013).This study is devoted to analyzing stress production in Arabic as produced by Cebuano learners in order to highlight the challenges so that teachers can address them in the best way. The data have been examined within the metrical theory of word stress elaborated in Hayes (1995). A sample of 100 words has been considered, spoken by six non-native speakers of Arabic, three females and three males, whose first language is Cebuano, the national language of the Philippines. Data analysis shows that native Cebuano speakers have an iambic foot, where the foot involves left-to-right parsing, satisfies the End Rule Right Principle by which the main stress lands on the head of the rightmost visible foot, and imposes a weak ban on the degenerate foot. Intriguingly, foot iambicity observed in the produced words is regarded as a reflection of the speakers’ source language (L1) that has an iambic foot. Arabic words spoken by Cebuano non-natives conform to the bimoraic condition for the minimal phonological word that takes the primary stress, and is repaired only through vowel lengthening; whereas gemination, as a main strategy for creating bimoraicity, is totally absent. Similarly, vowel lengthening is seen as a transfer effect of L1, where stress always attracts a long vowel. The results point to the great importance of prosody in teaching Arabic as a foreign language, since prosodic features significantly contribute to the communication intelligibility.